Predicting habitat suitability and connectivity for management and conservation of urban wildlife: A real‐time web application for grassland water voles. Issue 4 (14th February 2022) - Nelli, Luca; Schehl, Bianka; Stewart, Robyn A.; Scott, Catherine; Ferguson, Scott; MacMillan, Shelagh; McCafferty, Dominic J.
Abstract: Natural habitats in urban areas provide benefits for both humans and biodiversity. However, to achieve biodiversity gains, we require new techniques to determine habitat suitability and ecological connectivity that will inform urban planning and development. Using an example of an urban population of water voles Arvicola amphibius, we developed a habitat suitability model and a resistance‐surface‐based model of landscape connectivity to identify potential connectivity between areas of suitable habitat. We then updated the environmental variables according to new urban development plans and used our models to generate spatially explicit predictions of both habitat suitability and connectivity. To make models accessible to urban and conservation planners, we developed an interactive mapping tool that provided users with a graphical user interface (GUI) to inform conservation planning for this species. The model found that habitat suitability for water voles was related to the proportion and distance from key environmental variables, such as built‐up areas and urban green spaces, while the connectivity model identified important corridors connecting areas of potential distribution for this species. Future development plans altered the potential spatial distribution of the water vole population, reducing the extent of suitable habitat in some core areas. The interactive mapping tool made available suitable habitat and connectivity maps for conservation managers to assess new planning applications and for the development of a conservation action plan for water voles. Synthesis and applications . We believe this approach provides a framework for future development of nature conservation tools that can be used by planners to inform ecological decision‐making, increase biodiversity and reduce human–wildlife conflict in urban environments. Abstract : We believe this approach provides a framework for future development of nature conservation tools that can be used by planners to inform ecological decision‐making, increase biodiversity and reduce human–wildlife conflict in urban environments.